Sodium nitrite-derived nitric oxide protects rat testes against ischemia/reperfusion injury - Jae Won Lee; Dong-Hun Lee; Jae Keun Park; Jin Soo Han (Asian Journal of Andrology, 2019)
Testicular torsion, a common urologic emergency, is primarily caused by ischemia/reperfusion (I/R) injury of the testis. Nitric oxide (NO)-derived from nitrite (NO2−) has been reported to have prominent therapeutic effects on I/R injury in the heart, liver, and brain; however, its effects on testicular I/R injury have not been evaluated. This study, therefore, investigated whether NO from NO2− is beneficial in a rat model of testicular I/R injury which eventually results in impaired spermatogenesis. Male Sprague-Dawley rats were assigned to the following seven groups: group A, sham-operated control group; Group B, I/R with no treatment; Groups C, D, and E, I/R followed by treatment with three different doses of NO2−; Group F, I/R followed by administration of NO2− and NO scavenger (2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide potassium salt [C-PTIO]); and Group G, I/R followed by administration of nitrate (NO3−). NO2−, NO3−, and C-PTIO were intravenously administered. Histological examination of the testes and the western blot analysis of caspase-3 were performed. Levels of antioxidant enzymes and lipid peroxidation were measured. Germ cell apoptosis, oxidative stress, antioxidant enzymatic function, and lipid peroxidation in Group B were significantly higher than those in Group A. Group B exhibited an abnormal testicular morphology and impaired spermatogenesis. In contrast, testicular damages were attenuated in the NO2− treatment groups, which were caused by reduction in superoxide and peroxynitrite levels and an inhibition of caspase-3-dependent apoptosis. The results of this study suggest NO2− to be a promising therapeutic agent with anti-oxidant and anti-apoptotic properties in testicular I/R injury.